Smad Ubiquitination Regulatory Factor 2 Promotes Metastasis of Breast Cancer Cells by Enhancing Migration and Invasiveness - Jin, Chaoyang (2009)
Controlled protein degradation mediated by ubiquitin/proteasome system (UPS) plays a crucial role in modulating a broad range of cellular responses. Dysregulation of the UPS often accompanies tumorigenesis and progression. Here, we report that Smad ubiquitination regulatory factor 2 (Smurf2), a HECT-domain containing E3 ubiquitin ligase, is up-regulated in certain breast cancer tissues and cells. We show that reduction of Smurf2 expression with specific short interfering RNA in metastatic breast cancer cells induces cell rounding and reorganization of the actin cytoskeleton, which are associated with a less motile and invasive phenotype. Overexpression of Smurf2 promotes metastasis in a nude mouse model and increases migration and invasion of breast cancer cells. Moreover, expression of Smurf2CG, an E3 ligase–defective mutant of Smurf2, suppresses the above metastatic behaviors. These results establish an important role for Smurf2 in breast cancer progression and indicate that Smurf2 is a novel regulator of breast cancer cell migration and invasion.